Should the existing science of teams be applied to fluid teams? An exploration of fluid team effectiveness within the context of healthcare simulation - Grossman, Rebecca; Billotti, Brianna M.; Ha, Joseph J.; Cassara, Michael (Frontiers in Psychology, 2024)
Fluid teams have become increasingly prevalent and necessary for modern-day issues, yet they differ from more traditional teams, on which much of the current teams literature is based. For example, fluid teams are often comprised of members from different disciplines or organizational divisions who do not have a shared history or future, as they come together to perform a critical, time-sensitive task, and then disband. For these reasons, the mechanisms through which they function and perform may differ from those of more traditional teams, and research is needed to better understand these differences. To this end, this study utilized critical incident techniques and thematic analysis to examine fluid teams within healthcare, one of the primary contexts in which they are prevalent. Interdisciplinary faculty and students in the medical field who encounter fluid teams within simulation-based education were prompted to reflect on key factors that facilitate or hinder fluid team effectiveness. Primary themes extracted pertained to the conditions fluid teams operate within (e.g., high-stress), the behaviors and emergent states that contribute to their success (e.g., communication), and the KSAO's of value for members of fluid teams to possess (e.g., readiness). These themes were then compared to existing literature, yielding the identification of some similarities but also many important differences between fluid and traditional teams. A series of practical recommendations for how to promote fluid team effectiveness is then presented.